Mechanical Percussion Devices: A Survey of Practice Patterns Among Healthcare Professionals - Scott W Cheatham; Russell T Baker; David G Behm; Kyle Stull; Morey J Kolber (International Journal of Sports Physical Therapy, 2021)
# Background